Adaptive Spray and Wait Protocol for Vehicular DTN - Pandya, Vyomal; Bhargava Choubey, Shruti (International Journal of Engineering and Technology, 2018)
Because of high speed of vehicles, short contact durations and rapid changes in topology occurs in Vehicular Delay Tolerant Networks(VDTNs). This will generates few transmission opportunities and high and unpredictable delay. This problem can be solved by different routing protocol of VDTN . The VDTN protocol can be divided as single copy and multicopy. In single copy protocol the node is allowed to generate the unique copy of message and forward it on a unique path.The multi copy protocols generate and transmit the multiple copies of each message and forward it along various paths. If more number of copy spread in network there are more chances for successful transmission. The objective of paper is to improve performance of VDTN by modifying existing Spray and Wait protocol. In this paper we provide proposed algorithm for modify spray and wait protocol for improving delivery probability with different number of message copy. The modifications based on stored number of message copies at source/rely nodes and encountered nodes ratio.Â Â